4
$\begingroup$

I need to use the identity $\cos(3\theta)=4\cos^3(\theta)-3\cos(\theta) $ to solve the cubic equation $t^3+pt+q=0$ when $27q^2+4p^3<0$.

I believe I need to let $t=Acos(\phi)$ when $A=2\sqrt{\frac{-p}{3}}$, so that my equation looks more like the identity and I have $A^3\cos(\theta)^3+Ap\cos(\theta)+q=0$. Next I multiply by $\frac{4}{A^3}$ to get $4\cos(\theta)^3+\frac{4p}{A^2}cos(\theta)+\frac{4q}{A^3}=0$.

So then $4\cos(\theta)^3-3\cos(\theta)-\frac{3q}{Ap}=0$.

Now I am stuck and not sure what my next step is.

$\endgroup$
  • $\begingroup$ You have $\cos 3 \theta=3q/Ap.$ The next step is $3\theta =2\pi n \pm \arccos (3q/Ap)$ for some $n\in \mathbb Z.$ $\endgroup$ – DanielWainfleet Aug 31 '16 at 4:34
5
$\begingroup$

For a general cubic, $$ax^{3}+bx^{2}+cx+d=0$$ use what is known as the Tschirnhaus-Vieta approach: let $x=t+B$, then the cubic becomes $$t^3+\left(3B+\frac{b}{a}\right)t^2+\left(3B^2+\frac{c+2bB}{a}\right)t+\left(B^3+\frac{bB^2+cB+d}{a}\right)=0$$ By setting $B=-\frac{b}{3a}$, the coefficient of $t^2$ becomes zero and we obtain the depressed cubic $$t^3+pt+q=0 \tag{1}$$ where $$p=\frac{3ac-b^{2}}{3a^2},\qquad q=\frac{2b^3-9abc+27a^{2}d}{27a^3}$$ The quantity $\Delta=-4p^3-27q^2$ is called the discriminant of the cubic (1).

  • If $\Delta<0$, one root is real and two complex conjugate roots;
  • If $\Delta=0$ at least two roots coincide, and they are all real;
  • If $\Delta>0$ there are three unequal real roots.

Here we have $-\Delta=4p^3+27q^2<0$ and so $\Delta>0$ and we have three unequal real roots, also since $4p^3<-27q^2$ this implies $p<0$, and $p^3<0$, which is an equivalent condition for the three real roots. Now using the trigonometric identity: $$4\cos^3(\theta)-3\cos(\theta)-\cos(3\theta)=0 \tag{2}$$ transform the reduced cubic (1) to match (2). To do this let $t=A\cos(\theta)$ and substitute in to get $$A^3\cos^3(\theta)+Ap\cos(\theta)+q=0\tag{3}$$ Now multiply (3) by $\frac{4}{A^3}$ to give: \begin{align*} 4\cos^3(\theta)&+\frac{4p}{A^2}\cos(\theta)+\frac{4q}{A^3}=0\tag{4} \end{align*} To match (4) with (2) we need $\frac{4p}{A^2}=-3$, and so $A=2\sqrt{\frac{-p}{3}}$, hence we need $p<0$ for $A$ to be real, which we already have. Thus \begin{align*} 4\cos^3(\theta)&-3\cos(\theta)-\frac{3q}{Ap}=0 \end{align*} And so using (2) \begin{align*} \cos(3\theta)=\frac{3q}{2p}\sqrt{\frac{-3}{p}}=\frac{3q}{Ap}\tag{5} \end{align*} Now solve the trigonometric equation (5) as \begin{align*} \phi&=\arccos\left(\frac{3q}{Ap}\right) \end{align*} where $\phi$ is one angle that satisfies (5). The solutions for $3\theta$ are then $$3\theta=\pm \phi +2k\pi,\quad k\in\mathbb{Z},\,\,\, \phi\in[0,\pi]$$ from which the solutions for $\theta$ follow $$\theta=\frac{2k\pi\pm\phi}{3},\quad k\in\mathbb{Z},\,\,\, \phi\in[0,\pi]\tag{6}$$ We now find three distinct values for $\theta$ which relate to the roots, and are due to periodicity of the cosine function: so putting $k=0$, $1$, and $2$ into (6), and appealing to the fact that $\cos$ is an even function gives the three roots for (1) given by $t=A\cos(\theta)$ as: \begin{align*} t_1&=A\cos\left(\frac{\phi}{3}\right)\\ t_1&=A\cos\left(\frac{\phi+2\pi}{3}\right)\\ t_1&=A\cos\left(\frac{\phi+4\pi}{3}\right) \end{align*}

Remark 1: If $p>0$, then $\Delta=-4p^3-27q^2<0$, and there are two complex conjugate roots, with the real root given by: \begin{align*} \bar{A}&=2\sqrt{\frac{p}{3}}\\ \bar{\phi}&=\operatorname{arcsinh}\left(\frac{3q}{Ap}\right)\\ x_1&=-\bar{A}\sinh\left(\frac{\bar{\phi}}{3}\right) \end{align*} Remark 2: To transform back to $(\star)$ to find the solution for $x$, we initially set $x=t+B=A\cos(\theta)+B$, and so our roots for $(\star)$ are: \begin{align*} x_1&=A\cos(\theta_1)+B=A\cos\left(\frac{\phi}{3}\right)+B\\ x_2&=A\cos(\theta_2)+B=A\cos\left(\frac{\phi+2\pi}{3}\right)+B\\ x_3&=A\cos(\theta_3)+B=A\cos\left(\frac{\phi+4\pi}{3}\right)+B \end{align*}

$\endgroup$
2
$\begingroup$

Your next step is $$\cos3\theta=\frac{3q}{Ap}$$ Set $\alpha=\arccos\Bigl(\dfrac{3q}{Ap}\Bigr)$. You now have a trigonometric equation $\;\cos3\theta=\cos \alpha$, whence $$3\theta\equiv \pm\alpha\mod 2\pi\iff\theta=\pm\frac\alpha3\mod\frac{2\pi}3$$ There seems to be $6$ roots, but these roots are pairwise equal.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.